STUDI KAJIAN LAJU PERTUMBUHAN PENERIMAAN NEGARA DI SEKTOR PAJAK - Ady Sulaiman; Bakhtiar Efendi (ITB AAS Indonesia Surakarta, 2023)
In national development efforts, taxes are one of the important things that become a large and strategic source of revenue for the state, which is useful in increasing the growth of the country's economy to create prosperity and welfare for society and the state. Thus taxes become one of the sources of state revenue that has high potential. This study aims to determine the growth rate of realization of state revenue, the growth rate of realization of luxury goods value-added tax, and international trade tax. This study uses secondary data from 2017 to 2018 obtained from the Central Bureau of Statistics and the Directorate General of Taxes. The research method uses the growth rate calculation formula. The results showed that the growth rate of realization of state revenue in the tax sector has a unidirectional relationship with the realization of luxury goods value-added tax and international trade tax. If there is an increase in the growth rate of realization of luxury tax and the international The context of the application of luxury tax and international trade tax is expected to reflect horizontal and vertical equity in every tax collection, including other VAT collection. In order to reflect fairness, the collection of tax on the sale of luxury goods and international trade tax on international trade is expected to reflect horizontal and vertical equity in every tax collection, including the collection of other VAT.